Hybrid models of cell and tissue dynamics in tumor growth - Yangjin Kim; Hans G. Othmer (Mathematical Biosciences and Engineering)
Hybrid models of tumor growth, in which some regions are described at the celllevel and others at the continuum level, provide a flexible description thatallows alterations of cell-level properties and detailed descriptions of theinteraction with the tumor environment, yet retain the computational advantagesof continuum models where appropriate. We review aspects of the general approachand discuss applications to breast cancer and glioblastoma.